A convenient method for europium‐labeling of a recombinant chimeric relaxin family peptide R3/I5 for receptor‐binding assays. (22nd March 2013) - Zhang, Wei‐Jie; Jiang, Qian; Wang, Xin‐Yi; Song, Ge; Shao, Xiao‐Xia; Guo, Zhan‐Yun
Abstract : Relaxin family peptides have important biological functions, and so far, four G‐protein‐coupled receptors have been identified as their receptors (RXFP1–4). A chimeric relaxin family peptide R3/I5, containing the B‐chain of relaxin‐3 and the A‐chain of INSL5, is a selective agonist for both RXFP3 and RXFP4. In a previous study, europium‐labeled R3/I5, as a nonradioactive and low‐background receptor‐binding tracer, was prepared through a chemical synthesis approach. In the present study, we established a convenient alternative approach for preparing the europium‐labeled R3/I5 tracer based on a recombinant R3/I5 designed to carry a solubilizing tag at the A‐chain N‐terminus and a pyroglutamate residue at the B‐chain N‐terminus. Because of the presence of a single primary amine moiety, the recombinant R3/I5 peptide was site‐specifically mono‐labeled at the A‐chain N‐terminus by a diethylenetriaminepentaacetic acid/europium moiety through a convenient one‐step procedure. The diethylenetriaminepentaacetic acid/Eu 3+ ‐labeled R3/I5 bound both receptors RXFP3 and RXFP4 with high binding affinities and low nonspecific binding. Thus, we have presented a valuable nonradioactive tracer for future interaction studies on RXFP3 and RXFP4 with various natural or designed ligands. The present approach could also be adapted for preparing and labeling of other chimeric relaxin family peptides. Copyright © 2013 European Peptide Society and John Wiley & Sons, Ltd. Abstract : A chimeric relaxin family peptide R3/I5, containing the B‐chain of relaxin‐3 and the A‐chain of INSL5, was recombinantly prepared and site‐specifically labeled at the A‐chain N‐terminus by a diethylenetriaminepentaacetic acid/europium moiety. The labeled peptide bound the relaxin family peptide receptors RXFP3 and RXFP4 with high binding affinities and low nonspecific binding, representing a valuable nonradioactive receptor‐binding tracer. The present approach could also be adapted for preparing and labeling of other chimeric relaxin family peptides.